Students' perceptions of the peer-feedback experience in MOOCs. Issue 1 (2nd January 2021) - Kasch, Julia; van Rosmalen, Peter; Löhr, Ansje; Klemke, Roland; Antonaci, Alessandra; Kalz, Marco
ABSTRACT: Various studies advocate training students prior to a peer-feedback activity to ensure high quality of feedback. Next to investing in students' peer-feedback skills, it is important to focus on the underlying perceptions since perceptions influence learning behavior. We implemented an online peer-feedback training session in a massive open online course and examined students' perceptions of peer-feedback and training focusing on their willingness, perceived usefulness, perceived preparedness, and general attitude; and students' peer-feedback experience and its relation to their perception. Analysis of a perception survey from 259 students revealed that the amount of prior experience results in significant differences in students' perception. Students without prior peer-feedback experience scored higher on willingness, usefulness, preparedness, and general attitude compared to students with some prior experience. Those with a lot of experience showed the strongest positive perception scores. No significant differences for the effect of training on perception could be measured with the available data.